Evaluación de la actividad fotocatalítica del dióxido de titanio sensibilizado con colorantes naturales en la degradación de azul de metileno (2017)
In the present work, TiO2 was sensitized with natural dyes of the species Esenbeckia alata extracted and purified by Professor Carlos Andrés Coy Barrera of the New Granada Military University, with whom a collaborative association was realized to evaluate the photocatalytic activity of these, taking advantage of which have a higher absorbance range, in order to avoid using ultraviolet radiation and achieve activity under visible light.